Stress And Bio Signals: A Review of State of Art Techniques - Kumar, Chandan Jyoti (International Journal of Computer Sciences and Engineering, 2025)
Irrespective of internal or external factors when a person feels excessive pressure it reflects in his facial expression, speech and physiological behaviour signals. Instead of traditional questioner method of stress evaluation, researchers now a day’s take various audiovisual and bio-signals, like heartbeat rate, muscle activity, blood pressure (BP) and skin conductivity. Electroencephalogram (EEG), Electrocardiogram (ECG), Electromyogram (EMG), Respiration (RSP) and Skin Conductivity (SC) are highly used bio-sensors for capturing bio signals. ECG signal gives heart-beat rate, inter-beat interval, and heart rate variability (HRV). EMG sensor when fit at upper trapezius gives the reading of muscle contraction which may be correlated with emotional state. SC sensors provide conductance and resistance of the skin which can also be used as a feature of importance. A wide range of physiological features from various analysis domains, including time/frequency, entropy, geometric analysis, sub-band spectra, multi-scale entropy, etc. along with audiovisual feature, got research attention in the process to find the best stress-relevant features and to correlate them with stress level. This article makes a detailed discussion of effectiveness of various bio signals for stress level and emotional state detection.